Structural Brain Changes Following Left Temporal Low-Frequency rTMS in Patients with Subjective Tinnitus. (3rd June 2014) - Lehner, Astrid; Langguth, Berthold; Poeppl, Timm B.; Rupprecht, Rainer; Hajak, Göran; Landgrebe, Michael; Schecklmann, Martin
Abstract : Repetitive transcranial magnetic stimulation (rTMS) of the temporal cortex has been used to treat patients with subjective tinnitus. While rTMS is known to induce morphological changes in healthy subjects, no study has investigated yet whether rTMS treatment induces grey matter (GM) changes in tinnitus patients as well, whether these changes are correlated with treatment success, and whether GM at baseline is a useful predictor for treatment outcome. Therefore, we examined magnetic resonance images of 77 tinnitus patients who were treated with rTMS of the left temporal cortex (10 days, 2000 stimuli/day, 1 Hz). At baseline and after the last treatment session high-resolution structural images of the brain were acquired and tinnitus severity was assessed. For a subgroup of 41 patients, additional brain scans were done after a follow-up period of 90 days. GM changes were analysed by means of voxel based morphometry. Transient GM decreases were detectable in several brain regions, especially in the insula and the inferior frontal cortex. These changes were not related to treatment outcome though. Baseline images correlated with change in tinnitus severity in the frontal cortex and the lingual gyrus, suggesting that GM at baseline might hold potential as a possible predictor for treatment outcome.